Pengaruh Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan Studi pada Karyawan Hotel Kila Senggigi - Baiq Rafikasari Eka Yudiana; Mahyuddin Nasir; Mukmin Suryatni (Universitas Bumigora, 2022)
This study aims to determine the effect of job satisfaction and work motivation on employee performance at Kila Senggigi Hotel. The data collection method used is the census method using primary data collected directly from the respondents using a questionnaire. The type of research used in this research is associative research with a quantitative approach. The sample number in the study was 50 respondents. The analytical tool used is multiple linear regression analysis. using SPSS version 25. The results of the analysis show that: (1) job satisfaction has a positive and significant effect on employee performance, (2) work motivation has a positive and significant effect on employee performance. Keywords : Job satisfaction, work motivation, employee performance